IMPLEMENTASI LITERASI BUKU CERITA BERGAMBAR KE DALAM KEGIATAN DRAMA PADA SISWA KELAS 5 SD - Lirra Zanni; Daroe Iswatiningsih; Yuni Asih; Salam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the low reading interest among elementary school students by integrating picture storybooks into drama activities. The research aims to explore strategies for implementing picture storybook literacy through dramatization and to examine students’ responses to this approach. Using a qualitative descriptive method, the study was conducted with fifth-grade students at SD Negeri Kedungsari. Data were collected through participatory observation, documentation, and teacher reflection, and analyzed using Miles and Huberman’s interactive model. The findings reveal that the implementation process consists of three stages: preparation, dramatization, and reflection. In the preparation stage, teachers selected age-appropriate picture storybooks and facilitated shared reading sessions to stimulate imagination and comprehension. During dramatization, students adapted the stories into simple scripts and performed them in groups, enhancing verbal expression, creativity, and collaboration. The reflection stage allowed students to discuss moral values and learning experiences, reinforcing comprehension and metacognitive awareness. Results show that students demonstrated high enthusiasm, improved understanding of narrative texts, effective teamwork, and increased confidence in verbal and nonverbal expression. The integration of picture storybook literacy with drama not only strengthened reading skills but also fostered social interaction, empathy, and critical thinking. Overall, this approach proved effective in creating an engaging and meaningful literacy experience, supporting the development of 21st-century skills in elementary education.